A retextualização do escrito para o oral: uma pedagogia expressiva da palavra para atores - Marques, Murillo (2016)
The actor is the main agency in the theater, as without his theatrical action, the play is incomplete. By adapting a written text to an oral genre, the actor aims to establish a verisimilitude relation between the playwright's forged dialogue and spoken language. This way, the theatrical text, despite from seeming as an everyday speech, it is a literary production, structured and unfinished, inasmuch as it foresees the action and active voice of the actor for its attainment. Therefore, considering the perspective of converting written texts to oral genre, the present research will be based in the intersection between socio interactionist studies on Oral Literary, Conversation Analysis, Sociolinguistics, Psycholinguistics and the practical and theoretical work strands with the text on Theatrical Arts, so that it will evidence the linguistic, semantic, syntactic and prosodic mechanisms used by the actor when converting written genre to oral genre. To the present remark, the analyzed corpus will the class on Verbal Expression from the Drama Art School, institution founded by Alfredo Mesquita in 1948, which since this date contributes to graduating actors that are part of a Modern National Theater scenario